On Philosophy of Barbara Skarga: An Approach to Get to Know Her Life and Work - Bogaczyk-Vormayr, Małgorzata (ETHICS IN PROGRESS, 2018)
Barbara Skarga (1919–2009) was one of the most important Polish Philosophers of 20th century. She was an expert in classical and contemporary French (e.g. Comte, Bergson, Lévinas) and German Philosophy (e.g. Kant, Hegel, Heidegger). In this paper I present some important biographical facts (participation in organized resistance in Vilnius, interments in Gulags) as well Skarga’s philosophical, mostly sociopolitical and ethical, ideas. I called its philosophical concept “philosophy of difference”.